Analysis Discourse Narration Mysticism on Hirotada's YouTube Channel Radiant “Friends Segment Story" - Salsabillah, Aulia; Santoso, Didik Haryadi; Siva, Nur (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2025)
In the current era, technological advances have significantly transformed the way we communicate. Communication has become faster, more convenient, and user-friendly. The widespread accessibility of the internet across various societal groups has had a profound impact on the media landscape. This research focuses on the analysis of discourse content in the " Friends Story "segment on Hirotada Radifan's YouTube channel. The study employs a qualitative approach through discourse analysis as developed by Teun A. Van Dijk. This qualitative approach focuses on the general principles underlying the construction of meaning from social phenomena within society. Based on observations conducted by the researcher on several videos from Hirotada Radifan's YouTube channel, particularly in the " Friends Story " segment, the study utilizes Van Dijk's three dimensions of discourse analysis. This theoretical framework aids the researcher in addressing the research problem concerning how discourse shapes mystical narratives on Hirotada Radifan's YouTube channel in the " Friends Story " segment. These three dimensions include the text dimension, social cognition, and social context.